Simulation of biogas utilization effect on the economic efficiency and greenhouse gas emission: a case study in Isfahan, Iran - Afrooz Rahimi Ariae; Mehdi Jahangiri; Mehdi Haghgo Fakhr; Akbar Alidadi Shamsabadi (Center of Biomass & Renewable Energy, Diponegoro University, 2019)
Biomass is a type of renewable energy that, in despite of its potentials and advantages including simple production technology, decreasing environmental issues, and energy generation capacity at the consumption site, has not been sufficiently utilized in Iran. Since, due to statistics, Isfahan enjoys remarkable prospects in terms of wind, solar and biomass energies, a combined system of indigenous energy sources for powering a cattle farm has been investigated and evaluated in this study. To evaluate the possibility of the optimal system for comparative reasons, the HOMER software was used. The designed hybrid system was a wind-solar-biomass generator that used a battery saver as backup. Although it seems that wind and solar energies have the highest potential for energy generation in Isfahan, the results showed that biomass, by itself, can provide the required power for a cattle farm. In fact, biomass energy was more economically efficient than wind and solar energies. Owing to the low electricity cost, generated from fossil fuels, in Iran, relative to a large number of countries, the findings revealed that using biomass for generating the electricity of a cattle farm will compensate the expenses by the mid-15th year and will generate profit for 9.5 years later. The results also showed that the solar cell-based hybrid system is cheaper than the wind turbine-based one. Regarding the price of per kWh of electricity produced, the results showed that the biomass generator system with the price 0.12 /kWh is the cheapest, and the solar cell-based and wind turbine-based hybrid systems are 3.33% and 10.83% more expensive, respectively. The results can be used for electricity generation with minimum pollution and expenses in the same regions. ©2019. CBIORE-IJRED. All rights reserved